PLF Versus PLIF and the Fate of L5-S1: Analysis of Operative Nonunion Rates Among 3065 Patients with Lumbar Fusions from a Regional Spine Registry. Issue 10 (15th May 2021) - Guppy, Kern H.; Royse, Kathryn E.; Norheim, Elizabeth P.; Harris, Jessica E.; Brara, Harsimran S.
Abstract : Study Design: A retrospective cohort study with chart review. Objective: The aim of this study was to compare the reoperation rates for symptomatic nonunions (operative nonunion rates) between posterolateral fusions with pedicle screws (PLFs) and posterior interbody fusion with pedicle screws (PLIFs). Summary of Background Data: Although radiographic nonunions in PLFs and PLIFs are well documented in the literature, there is no consensus on which technique has lower nonunions. Since some radiographic nonunions may be asymptomatic, a more clinically useful measure is operative nonunions, of which there is minimal research. Methods: A retrospective cohort study, using data from the Kaiser Permanente Spine Registry, identified adult patients (≥18 years' old) who had elective single and multilevel PLFs and PLIFs. Descriptive statistics and 2-year incidence rates for operative nonunions were calculated by fusion-level (1–3), fusion type (PLF vs. PLIF), and levels fused (L3 to S1). Time-dependent multivariable Cox-Proportional Hazards regression was used to evaluate nonunion reoperation rates with adjustment for covariates. Results: The cohort consisted of 3065 patients with PLFs (71.6%) and PLIFs (28.4%). Average age was 65.0 ± 11.7, average follow-up time was 4.8 ± 3.1 years, and average time to operative nonunion was 1.6 (±1.3) years. Single and multilevel incidence rates for nonunions after PLF versus PLIF were similar except for three-level fusions (2.9% [95% confidence interval, CI = 1.0–6.7] vs. 7.1% [95% CI = 0.2–33.9]). In adjusted models, there was no difference in risk of operative nonunions in PLIF compared to PLF (hazard ratio [HR]: 0.8, 95% CI = 0.4–1.6); however, patients with L5-S1 constructs with PLFs had 2.8 times the risk of operative nonunion compared to PLIFs (PLF: HR = 2.8, 95% CI = 1.3–6.2; PLIF: HR = 1.5, 95% CI = 0.4–5.1). Conclusion: In a large cohort of patients with >4 years of follow-up, we found no difference in operative nonunions between PLF and PLIF except for constructs that included L5-S1 in which the risk of nonunion was limited to PLF patients. Level of Evidence: 3